Learn how to interpret and use intracranial EEG findings - Frauscher, B; Mansilla, D; Abdallah, C; Astner-Rohracher, A; Beniczky, S; Brazdil, M; Gnatkovsky, V; Jacobs, J; Kalamangalam, G; Perucca, P; Ryvlin, P; Schuele, S; et al. (Epileptic disorders, 2024)
Epilepsy surgery is the therapy of choice for many patients with drug-resistant focal epilepsy. Recognizing and describing ictal and interictal patterns with intracranial electroencephalography (EEG) recordings is important in order to most efficiently leverage advantages of this technique to accurately delineate the seizure-onset zone before undergoing surgery. In this seminar in epileptology, we address learning objective "1.4.11 Recognize and describe ictal and interictal patterns with intracranial recordings" of the International League against Epilepsy curriculum for epileptologists. We will review principal considerations of the implantation planning, summarize the literature for the most relevant ictal and interictal EEG patterns within and beyond the Berger frequency spectrum, review invasive stimulation for seizure and functional mapping, discuss caveats in the interpretation of intracranial EEG findings, provide an overview on special considerations in children and in subdural grids/strips, and review available quantitative/signal analysis approaches. To be as practically oriented as possible, we will provide a mini atlas of the most frequent EEG patterns, highlight pearls for its not infrequently challenging interpretation, and conclude with two illustrative case examples. This article shall serve as a useful learning resource for trainees in clinical neurophysiology/epileptology by providing a basic understanding on the concepts of invasive intracranial EEG.
Keywords: Seizures; Epilepsy; pathology; epilepsie; Humans; seizure-onset pattern; dítě; Child; Epilepsies, Partial; Drug Resistant Epilepsy; elektrokortikografie; záchvaty; intracranial electroencephalography; lidé; elektroencefalografie; atlas; refrakterní epilepsie; epilepsie parciální; stereo-electroencephalography; low-voltage fast activity; Electroencephalography; interictal epileptiform discharges; Electrocorticography; prognosis